The impact of the death criterion on the WSN lifetime using EM pollution monitoring algorithm - Nouh, Sara (AUC Knowledge Fountain, 2017)
Wireless sensor networks (WSNs) are one of the most advanced means that are used for monitoring and reporting. The fact that they consist of small, low cost sensor nodes that are continuously used in a variety of applications has made them become a very attractive field in research. One of the main applications of interest in this research is monitoring the electromagnetic (EM) pollution caused by the rapid expansion of electronic and wireless devices. Research has proven that radiations that these devices emit have a huge effect on the human’s health and therefore are worth monitoring. An advanced algorithm was developed in order to monitor these emissions and its main parameters were randomized to give the algorithm a room of flexibility to suit a variety of monitoring scenarios. Although WSNs are used in numerous critical applications, they still face some challenges. Relying on battery-operated sensors causes the network to be resource constrained and therefore, there is a continuous need for prolonging the network lifetime. In this thesis, different death criteria will be applied and their effect on the network lifetime will be investigated. Moreover the impact of changing the number of sensing cycles per network master will be investigated, since the main aim is to exploit the sensor’s energy efficiently. Finally, the selection of network master will be examined, i.e., random vs. planned to evaluate its effect on the previous simulations and more importantly on the network lifetime.